Natural Light in Interior Architecture: Enhancing Mental Health - Negarestan, Alireza (Management Strategies and Engineering Sciences, 2025)
This study aims to explore the influence of natural light in interior architecture on mental health, highlighting architectural strategies that optimize daylight exposure to enhance psychological well-being. A scientific narrative review method was employed, analyzing scholarly articles published between 2015 and 2025 from databases such as Scopus, Web of Science, and ScienceDirect. The selection criteria focused on studies related to natural light in architectural design and its psychological effects, using thematic analysis to synthesize key findings on the relationship between daylight exposure and mental health. The review reveals that natural light significantly enhances mood, reduces stress, and improves cognitive performance by regulating circadian rhythms and promoting visual comfort. Architectural strategies such as large windows, skylights, atriums, and reflective surfaces are effective in maximizing daylight exposure. The findings highlight that natural light contributes to mental well-being in various settings, including workplaces, educational institutions, healthcare facilities, and residential spaces, underscoring its importance in human-centric architectural design. Integrating natural light into architectural design is essential for creating environments that support mental health. Thoughtful spatial design that prioritizes daylight exposure enhances well-being, cognitive function, and emotional resilience, making it a critical consideration in contemporary architecture.